2023
DOI: 10.1002/smll.202306178
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Shell Thickness Engineering in Pd3Pb@Pt Bifunctional Electrocatalyst for Ethanol Upgrading Coupled with Hydrogen Production

Tong Li,
Qiuxia Wang,
Jingjing Wu
et al.

Abstract: The ethanol oxidation reaction (EOR) is an attractive alternative to the sluggish oxygen evolution reaction in electrochemical hydrogen evolution cells. However, the development of high‐performance bifunctional electrocatalysts for both EOR and hydrogen evolution reaction (HER) is a major challenge. Herein, the synthesis of Pd3Pb@Pt core–shell nanocubes with controlled shell thickness by Pt‐seeded epitaxial growth on intermetallic Pd3Pb cores is reported. The lattice mismatch between the Pd3Pb core and the Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[11][12][13] Welldesigned core-shell structures can not only facilitate the modulation of the electronic structure of catalysts to optimize H* adsorption behavior but also increase the number of exposed active sites, thereby enhancing the intrinsic catalytic activity. [14][15][16] For instance, Zhang et al reported various Pd@Ir core-shell nanostructures with well-defined fcc-2H-fcc heterophases which exhibit excellent catalytic performance toward HER. The modified electronic structures of Ir in the fcc-2H-fcc heterophases can provide large amounts of high-index facets, step sites and uncoordinated atoms on the surface of the nanodendrites, providing abundant active sites and optimizing the adsorption energy towards the intermediate H* to improve the HER performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Welldesigned core-shell structures can not only facilitate the modulation of the electronic structure of catalysts to optimize H* adsorption behavior but also increase the number of exposed active sites, thereby enhancing the intrinsic catalytic activity. [14][15][16] For instance, Zhang et al reported various Pd@Ir core-shell nanostructures with well-defined fcc-2H-fcc heterophases which exhibit excellent catalytic performance toward HER. The modified electronic structures of Ir in the fcc-2H-fcc heterophases can provide large amounts of high-index facets, step sites and uncoordinated atoms on the surface of the nanodendrites, providing abundant active sites and optimizing the adsorption energy towards the intermediate H* to improve the HER performance.…”
Section: Introductionmentioning
confidence: 99%
“…Under an applied voltage of only ~0.1 V, both the cathode and anode can simultaneously generate H 2 [ 17 ]. We have also demonstrated the viability of the oxidation of other small molecules such as ethanol, methanol, urea, formate, and ethylene glycol [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%